2023
DOI: 10.3390/biom13071065
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Topical 1,25 and 24,25 Vitamin D on Diabetic, Vitamin D Deficient and Vitamin D Receptor Knockout Mouse Corneal Wound Healing

Abstract: Delayed or prolonged corneal wound healing and non-healing corneas put patients at risk for ocular surface infections and subsequent stromal opacification, resulting in discomfort or visual loss. It is important to enhance corneal wound healing efficiency and quality. Vitamin D (Vit D) is both a hormone and a vitamin, and its insufficiency has been linked to immune disorders and diabetes. For this study, wound healing and recruitment of CD45+ cells into the wound area of normoglycemic and diabetic mice were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…The current study found that CD45+ cells with a dendriform morphology were significantly decreased in the basal epithelial layer of wounded diabetic mouse corneas compared to normoglycemic mice, with topical 24,25 Vit D increasing their numbers. These results are in agreement with an earlier study from our laboratory in which the corneas received only an epithelial abrasion with no stromal damage, and cells were counted at the level of the highest cell density, as opposed to the basal epithelium, where corneal nerves terminate [19]. Pertinant to the current study, it has been shown that CD45+ cells and macrophages play a pivotal role in the mechanisms involved in peripheral nerve regeneration and degeneration [56].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The current study found that CD45+ cells with a dendriform morphology were significantly decreased in the basal epithelial layer of wounded diabetic mouse corneas compared to normoglycemic mice, with topical 24,25 Vit D increasing their numbers. These results are in agreement with an earlier study from our laboratory in which the corneas received only an epithelial abrasion with no stromal damage, and cells were counted at the level of the highest cell density, as opposed to the basal epithelium, where corneal nerves terminate [19]. Pertinant to the current study, it has been shown that CD45+ cells and macrophages play a pivotal role in the mechanisms involved in peripheral nerve regeneration and degeneration [56].…”
Section: Discussionsupporting
confidence: 93%
“…CD45+ cells and macrophages in the basal epithelium were immunostained after the corneas were wounded as described above and treated with 1,25 Vit D or 24,25 Vit D three times over 8 h. CD45 and F4/80 antibodies were used to immunolabel hematopoieticderived immune cells and macrophages, respectively [19,39,40]. The eyes were fixed with Zamboni fixative (American MasterTech Scientific, Lodi, CA, USA) for 75 min and then washed three times with PBS.…”
Section: Immunostaining For CD 45+ Cells and Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the Zhang laboratory conducted a clinical trial demonstrating the efficacy of topical vitamin D 3 in treating chloasma, a condition of hypermelanosis occurring during pregnancy, as well as in enhancing wound healing outcomes [28]. In another study, the Watsky laboratory found that both topical 1,25(OH) 2 D 3 and 24,25(OH) 2 D 3 accelerate corneal wound healing in mice [29]. Additionally, in a recent review, Bikle emphasized the importance of vitamin D and calcium signaling in epidermal wound healing, highlighting their role in stem cell activation and re-epithelialization [30].…”
Section: Skin As a Mediator Of The Synthesis Of Vitamin Dmentioning
confidence: 99%